2021
DOI: 10.1186/s13229-021-00455-5
|View full text |Cite
|
Sign up to set email alerts
|

Autism symptoms in anorexia nervosa: a comparative study with females with autism spectrum disorder

Abstract: Background Recent research suggests a link between autism spectrum disorder (ASD) and anorexia nervosa (AN). Individuals with AN show high scores on measures of ASD symptoms, relative to individuals without AN, however, there are currently no studies directly comparing women with AN to women with ASD. The aim of the current study was to examine profiles of ASD symptoms in young women in the acute and recovered stages of AN, women with ASD, and typically developing controls (TD), on both self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 75 publications
3
27
2
Order By: Relevance
“…Our behavioural results found that the AAN group had increased scores for ADOS-2 domain scores in communication and creativity domains with medium to large effect size compared to HC group, with the WR group in-between. This replicates previous work which has found that individuals with AAN have increased ADOS-2 scores, similar to that of autistic individuals when compared to HC, with WR individuals lying between groups (Kerr-Gaffney et al, 2021). Interestingly, our results demonstrated that WR individuals had increased stereotype and repetitive behaviours (SRB) compared to AAN and HC individuals with a medium effect size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our behavioural results found that the AAN group had increased scores for ADOS-2 domain scores in communication and creativity domains with medium to large effect size compared to HC group, with the WR group in-between. This replicates previous work which has found that individuals with AAN have increased ADOS-2 scores, similar to that of autistic individuals when compared to HC, with WR individuals lying between groups (Kerr-Gaffney et al, 2021). Interestingly, our results demonstrated that WR individuals had increased stereotype and repetitive behaviours (SRB) compared to AAN and HC individuals with a medium effect size.…”
Section: Discussionsupporting
confidence: 92%
“…A potential reason for this could be the use of self-report questionnaires verses objective interviews. Our study and studies that have used the ADOS-2 have found increased SRB scores (Kerr-Gaffney et al, 2021) compared to studies using self-reported measures (Kerr-Gaffney et al, 2021). As autistic women and men have different repetitive interests (Lai et al, 2015), it may be that current tools are not sensitive enough to pick up differences.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In fact, many women have been identified as autistic following diagnosis of eating disorders [83]. AN and autism have many parallels, with both groups displaying aloofness, rigidity, RRBs, and social impairment [84,85]. Females with anorexia tend to have elevated autistic traits [85,86], thereby making it hard to distinguish whether the displayed phenotypes are part of AN or there is a co-occurrence of autism.…”
Section: Associated Conditionsmentioning
confidence: 99%
“…AN and autism have many parallels, with both groups displaying aloofness, rigidity, RRBs, and social impairment [84,85]. Females with anorexia tend to have elevated autistic traits [85,86], thereby making it hard to distinguish whether the displayed phenotypes are part of AN or there is a co-occurrence of autism. One important distinguishing factor between the two conditions is the quality of social response: difficulties in social reciprocity is prevalent in ASD, while those suffering from AN show little difficulty in understanding social prompts [85,87].…”
Section: Associated Conditionsmentioning
confidence: 99%